Correlation analysis on physicochemical and structural properties of sorghum starch - Yan, Shouxin; Li, Zhao; Wang, Bin; Li, Tingting; Li, Zhiyang; Zhang, Nan; Cui, Bo (Frontiers in Nutrition, 2023)
Abstract: This paper analyzed physicochemical and structural properties of 30 different types of sorghum starches based on their apparent amylose content (AAC). Current results confirmed that sorghum starch exhibited irregular spherical or polygonal granule shape with 14.5 μm average particle size. The AAC of sorghum starch ranged from 7.42% to 36.44% corresponding to relative crystallinities of 20.5% to 32.4%. The properties of enthalpy of gelatinization (ΔH), peak viscosity (PV), relative crystallinity (RC), degree of double helix (DD), degree of order (DO), and swelling power (SP) were negatively correlated with AAC, while the cool paste viscosity (CPV) and setback (SB) were positively correlated with AAC. Correlations analyzed was conducted on various physicochemical parameters. Using principal component analysis (PCA) with 20 variables, the difference between 30 different types of sorghum starch was displayed. Results of current study can be used to guide the selection and breeding of sorghum varieties and its application in food and non-food industries.